THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN INCREASING THE INCOME OF THE POPULATION AND IN THE DEVELOPMENT OF THE COUNTRY'S ECONOMY - Rashidov Abror Ro‘zimurod o‘g‘li; Mamadaliyev Muslimbek Zohidjon o‘g‘li (Zeta Repository, 2023)
We will discuss what is the role of small business and entrepreneurship in increasing the income of the population in the Republic of Uzbekistan in this article and what the importance that is in improving the living conditions of the population is.